Analisis Kemampuan Pemecahan Masalah Matematika Ditinjau Dari Gaya Kognitif Reflektif dan Impulsif Siswa Kelas VII.B SMPN 4 Solok Selatan - Shinta Hidayah; Alfi Yunita; Audra Pramitha Muslim (STKIP PGRI Sumatera Barat, 2022)
ABSTRACT This research is motivated by the low ability of students’ mathematical problem solving and students’ cognitive style in solving problems. the purpose of this study was to determine how thw mathematical problem solving ability in term of the reflective abd impulsive cognitive style of class VIIB students of SMPN 4 South Solok. This type of research is descriptive research with a qualitative approach. The sampling technique used was purposive sampling. The research instrument was in the form the Matching Familiar Figure Test (MFFT), mathematics problem-solving ability test and interviews. Data analysis techniques using qualitative data analysis techniques are data reduction, data presentation and drawing conclusios. The result showed that who had the criteria of problem solving ability and reflective cognitive style of class VIIB students as many as 9 people consisting of 1 person who had low and very low problem solving ability criteria. Students who have the criteria of problem solving ability and cognitive style of class VIIB students are 6 people sonsiting of 1 person who has low problem solving ability criteria and very low people.ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya kemampuan pemecahan masalah matematika siswa dan gaya kognitif siswa dalam menyelesaikan masalah. Tujuan penelitian ini adalah untuk mengetahui bagaimana kemampuan pemecahan masalah. Tujuan penelitian ini adalah untuk mengetahui bagaimana kemampuan pemecahan masalah matematika ditinjau dari gaya kognitif dan impulsive siswa kelas VIIB SMPN 4 Solok Selatan. Jenis penelitian deskriptif dengan pendekatan kualitatif. Teknik pengambilan sampel menggunakan purposive sampling. Instrumen penelitian berbentuk tes Matching Familiar Figure Test (MFFT), tes kemampuan pemecahan masalah matematika dan wawancara. Teknik analisis data yang menggunakan teknik analisis data kualitatif yaitu reduksi data, penyajian data dan penarikkan kesimpulan. Hasil penelitian menunjukkan bahwa siswa yang memiliki kriteria dari kemampuan pemecahan masalah dan gaya kognitif reflektif siswa kelas VIIB 9 orang yang terdiri 1 orang memiliki kriteria kemampuan pemecahan masalah rendah dan sangat rendah 8 orang. Siswa yang memiliki kriteria kemampuan pemecahan masalah dan gaya kognitif impulsive kelas VIIB sebanyak 6 orang yang terdiri 1 orang yang memiliki kriteria kemampuan pemecahan masalah rendah dan sangat rendah 5 orang.